Human capital, technology intensity, and growth in a regional context - Favaro, Donata; Ninka, Eniel; Turvani, Margherita (Argomenti, 2018)
In this study, we develop an empirical analysis of the pattern of growth in one of the Italian best performing regions—the Veneto region—focusing mainly on the role played by human capital employed in sectors with different technological intensities. To do so, we build up an original dataset by merging data available at a very local level (Local Labour Systems-LLS) with our elaborations on data from an employee-employer dataset made available by the Local Labour Agency. The latter dataset includes all employment spells in the Veneto region. This original datasets are used to construct aggregate variables and to estimate growth equations for the cross-section of the Venetian LLSs. The results underline how growth in the Veneto region is positively affected by human capital employed in medium and medium-low technology industries.